Compactive Deformation of Sandstone Under Crustal Pressure and Temperature Conditions. Issue 4 (8th April 2021) - Jefferd, Mark; Brantut, Nicolas; Meredith, Philip G.; Mitchell, Thomas M.; Plümper, Oliver
Abstract: The transition from macroscopically brittle to macroscopically ductile deformation in porous sandstones is known to be pressure dependent, with compactive, ductile behavior occurring only once significant effective pressures have been reached. Within the crust, such effective pressures are associated with burial depths in the range 0.5–6 km, where the temperature is likely 35°C–200°C. To test the importance of such elevated temperature on the strength and deformability of sandstone, a series of constant strain rate, triaxial deformation experiments were performed on three different water saturated sandstones at either ambient temperature or 150°C. For each sandstone, an effective pressure range was used which spanned both the brittle and ductile deformation regimes, up to a maximum of 120 MPa. In the brittle regime, we observed a temperature‐dependent lowering of the yield stress of between 8% and 17%. Within the ductile regime, we observed an even greater reduction in the yield stress of between 9% and 37%. A further notable observation is that the transition from dilatant, brittle behavior to compactive, ductile behavior tends to occur at a lower effective pressure at elevated temperature. The weakening observed at elevated temperature can be explained by a reduction in fracture toughness, which is shown mathematically to cause greater weakening in the ductile regime than in the brittle regime. The apparent reduction in fracture toughness at elevated temperature is potentially driven by a combination of a reduction in surface energy and, to a minor extent, an increase in subcritical crack growth rate. Key Points: Increase in temperature to 150°C lowers both yield stress and absolute strength of sandstone The weakening is greater in the ductile regime than in the brittle regime A lowering of the fracture toughness can explain the observed weakening